MODAL SOSIAL, STRATEGI KOPING EKONOMI, DAN KESEJAHTERAAN OBJEKTIF KELUARGA DENGAN PEREMPUAN SEBAGAI KEPALA KELUARGA - Kabbaro, Hurriyyatun; Hartoyo, Hartoyo; Yuliati, Lilik Noor (Jurnal Ilmu Keluarga dan Konsumen, 2014)
Number of female-headed families tended to increase in Indonesia. The new family structures with maternal functions simultaneously as head of the family led to various adjustments, especially to maintain the family welfare. This research was aimed to analyze social capital, economic coping strategy, and objective well-being of female-headed families. This research held in Bogor District and used cross sectional design. This research involved 53 female-headed families who have been became single-parent since last two years. The families were chosen by snowball sampling and the data was obtained by interview using questionnaire. The result showed that more than half of female-headed families had income over the poverty line. Analysis of logistic regressiondiscovered female-headed’s age had significant chance to have positive influence on family objective well-being. Family objective well-being was influenced by social capital variable particularly in dimension of trust and social network. This research estimated that decreasing of cutting back expenses strategy will give higher chance to identify family to be more prosperous objectively.